CFD investigation of pressure drop reduction in hydrotransport of multisized zinc tailings slurry through horizontal pipes. (19th May 2023) - Krishna, Ram; Kumar, Niranjan; Gupta, Pankaj Kumar
Abstract: Zinc is an important metal useful in hydrogen production. Mining of zinc also involves zinc tailings disposal using pipeline transportation which is an energy- and water-intensive process. In this study, the multisized slurry of zinc tailings is modeled using CFD to investigate the flow field characteristics in a straight horizontal pipe fitted with swirl-inducing sections. The primary objective was to study the pressure drop by adding swirl-inducing pipe of different numbers of lobes to the conventional pipe. Nine configurations of multi-lobed swirl-inducing pipes were studied for transport characteristics of solids at three flow rates and three overall solids concentrations. Eulerian-Eulerian modeling with the RNG k-ε turbulence model is employed for simulations. The numerical model is validated for pressure drop against available experimental results, and excellent agreement is achieved. The study shows that 10-lobed swirl-inducing section fitted to the conventional pipe reduces the pressure drop by nearly 35%, offering the potential for further exploration. Highlights: Swirl-inducing motion is utilized for reducing settling of solid particle in pipeline. The slurry is modeled as multi-sized particles considering six size classes. Nine configurations of lobed swirl pipes for dense slurries. The 10 lobed swirl-inducing pipe is found to reduce pressure drop by approximately 35% as compared with the conventional pipe.